The Involvement of Noradrenaline in Rapid Eye Movement Sleep Mentation - Gottesmann, Claude (Frontiers in Neurology, 2011)
Noradrenaline, one of the main brain monoamines, has powerful central influences on neurobiological processes in the forebrain which support the mental activities occurring during the sleep–waking cycle. Noradrenergic neurons are activated during waking, decrease their firing rate during slow wave sleep, and become silent during REM sleep. Although a low level of noradrenaline is still maintained during REM sleep, the decrease observed during this period contributes to the mentation disturbances that occur with dreaming, which principally resemble symptoms of schizophrenia but seemingly also of attention deficit hyperactivity disorder.